The foodscapes of children and adolescents attending schools in Lima, Peru - Rozas Urrunaga, Lucila Jimena (2022)
Foodscapes are the sum of all places where food and eating are actualized, as well as the institutional arrangements, discourses, cultural practices, trends and meanings that shape the relationship between individuals and food. However, limited research is available on how the different elements of foodscapes (physical, social, institutional) interact to influence children's and adolescents' eating behaviors. The aim of this study was to identify and characterize the factors influencing Peruvian children's and adolescents' practices around food, focusing on the systemic and complex nature of eating. We conducted non-participant observations inside and around two schools—one public and one private—located in Lima, Peru, for an entire school-week, and interviewed 44 parents/caregivers of children and adolescents, ages 6–16. Qualitative content analysis was developed, as its iterative and reflective nature allowed for evolving understandings of the data. Results showed that individual attributes (SES, age and gender) interact with individual agency, the physical environment, parental and peer influence, to determine differentiated food-related outcomes of children and adolescents. Moreover, the state-wide law aiming to protect children's and adolescents' health and nutrition seemed to partially influence the eating practices of parents and children at school and at home. This study is unique in its kind, as existent research has mainly focused on the effects of foodscapes on children and adolescents in Western countries, while research in the Global South, such as Peru, remains mostly underdeveloped. Moreover, this study, unlike previous ones, intends to systematically understand how foodscapes shape children's and adolescents' eating practices.